Забезпечення прав національних меншин у контексті президентських виборів - Лойко, Л.І. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Анализируются проблемы современной государственной этнонационалъной политики Украины, вызовы для ее полиэтнического общества в условиях президентской выборной кампании. The problems of modern state ethno-national policy of Ukraine, challenges for its poly-ethnic society in the conditions of presidential elective campaign are analyzed in the article.